99mTc-sulfid und die Szintillationskamera zur Schnelldiagnose des Perikardergusses - Weiss, E.; Blahd, W. H.; Winston, M. A.; Krishnamurthy, G. T.; Thomas, P. B. (Nuklearmedizin - NuclearMedicine, 1971)
Because of its speed, accuracy, and reproducibility, radioisotopic angiocardiography appears to be the method of choice for the diagnosis of pericardial effusion. Technetium-99m sulfide is preferable to 99mTc sodium pertechnetate in these studies for the following reasons: (1) its specific uptake by the liver aids both in patient positioning and in the accuracy of diagnosis; and (2), studies can be repeated within 15—20 minutes should there be equiment or technical error.